Methoxydiphenylamine-substituted fluorene derivatives as hole transporting materials: role of molecular interaction on device photovoltaic performance - Robertas Tiazkis (Nature Portfolio, 2017)
Abstract The molecular structure of the hole transporting material (HTM) play an important role in hole extraction in a perovskite solar cells. It has a significant influence on the molecular planarity, energy level, and charge transport properties. Understanding the relationship between the chemical structure of the HTM's and perovskite solar cells (PSCs) performance is crucial for the continued development of the efficient organic charge transporting materials. Using molecular engineering approach we have constructed a series of the hole transporting materials with strategically placed aliphatic substituents to investigate the relationship between the chemical structure of the HTMs and the photovoltaic performance. PSCs employing the investigated HTMs demonstrate power conversion efficiency values in the range of 9% to 16.8% highlighting the importance of the optimal molecular structure. An inappropriately placed side group could compromise the device performance. Due to the ease of synthesis and moieties employed in its construction, it offers a wide range of possible structural modifications. This class of molecules has a great potential for structural optimization in order to realize simple and efficient small molecule based HTMs for perovskite solar cells application.